PERBINCANGAN PENDIDIKAN KARAKTER - Renata Renata; Muhammad Kristiawan; Fatmi Andi Rizki Pratami (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
The availability of characteristic human resources is a vital necessity. This is done to prepare for global challenges and national competitiveness. The problem is Indonesia's human resources do not reflect the expected educational aspirations. For example, there are many students who cheat when they do examination, being lazy, brawl between fellow students, performing promiscuity, drugs abuse, and others. On the other hand, found teachers who always provide bad examples to their students. The teachers often do frauds in certification and they upload bad videos on social media. This article was a library research, which investigated the debate of educational character. The educational character is the deliberate use of all dimensions of school life to foster optimal character development. For educational character in schools, all educational stakeholders should be involved such the education itself, curriculum content, learning and assessment processes, handling or management of subjects, school management, implementation of co-curricular activities, empowerment infrastructure, financing, and work ethic of all school residents. In addition, educational character is interpreted as a behavior of school residents. Educational character is a system on planting character values for learners, which contains knowledge, individual consciousness, and the willingness to perform God’s values and being insan kamil.